Emerging Players in Global Mining - Humphreys, David (World Bank, Washington, DC, 2014)
Companies from the emerging economies are a growing feature of the global mining industry. This document looks at who these companies are and the factors behind their growth. The contribution of the emerging economies to the global supply of minerals since 2000 is striking. With their growth in production exceeding that of the advanced economies in almost every commodity, the share of these countries in global mineral production mounted steadily. Several factors have combined to provide a boost to the role and fortunes of emerging economy companies in mining over recent years. Five of the most important are: (i) market liberalization and privatization of state-owned companies; (ii) privileged access of local companies to significant and underdeveloped local resources; (iii) strong financial positions due to the mining boom of 2003-2008; (iv) drive for geographic and commodity diversification, at times with tacit support of respective home governments; and (v) strategic expansion, usually to ensure raw material supplies for their metallurgical operations. The role of the emerging economy countries, and of companies based in these countries, is going to become increasingly important to the minerals industry in coming years.